Определение минимально необходимой концентрации присадки Infineum C9425 в масле И-Г-А-32 для гидроприводов строительных и дорожных машин - Венцель, Е. С.; Щукин, А. В.; Краснокутский, Максим Владимирович (Харківський національний університет Повітряних Сил ім. Івана Кожедуба, 2010)
Приведены методика и результаты испытаний на машинах трения ЧШМ и СМЦ-2 масла И-Г-А-32, применяемого в гидроприводах строительных и дорожных машин в качестве рабочей жидкости. Показано, что значение минимально необходимой концентрации искусственно введенной в масло противоизносной присадки Infineum С9425 должно составлять не менее 0,45%, что обеспечивает наименьший износ трущихся пар при работе их в режимах смешанного и граничного трения.

A method and results of tests is resulted on the machines of friction of CHSHM and SMC-2 of butter of I-G-A-32, applied in hydraulic actuators of build and travelling machines as a working liquid. It is rotined that a value is minimum the necessary concentration of the antiwear additive of Infineum S9425 artificially entered in butter must make no less than 0,45%, that provides the least wear of the ground pair during work them in the modes of the mixed and border friction.
Determination is minimum the necessary concentration of additive of Infineum S9425 in butter of I-G-A-32 for гидроприводов of build and travelling machines
Keywords: машиностроение; индустриальное масло И-Г-А-32; электрическая энергия; механика; concentration of additive; wear of elements hydraulic actuator of SDM; hydraulic actuators of build and travelling machines